2012
DOI: 10.1021/ef2016683
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Laminar Burning Velocity of Methanol Flames

Abstract: To better understand and predict the combustion behavior of methanol in engines, sound knowledge of the effect of the pressure, unburned mixture temperature, and composition on the laminar burning velocity is required. Because many of the existing experimental data for this property are compromised by the effects of flame stretch and instabilities, this study was aimed at obtaining new, accurate data for the laminar burning velocity of methanol−air mixtures. Non-stretched flames were stabilized on a perforated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…Liao et al [20] reported laminar burning velocities using the spherical combustion bomb technique for methanol/'air' mixtures at 358 K. Veloo et al [21] experimentally determined the laminar flame speed of methanol using the counter-flow configuration technique at atmospheric pressure and at an unburned mixture temperature of 343 K. Vancoillie et al [22] reported laminar flame speed measurements at atmospheric pressure for methanol/'air' mixtures at unburned gas temperatures of 298-358 K using the heat flux method. What is absent for the most part in the previous studies is validation data for engine relevant conditions at pressures in the range 10-150 atm in the temperature range 800-1600 K. This study provides a comprehensive set of data in this regime and covers low-to high-temperature chemistry by coupling ST, RCM and JSR measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al [20] reported laminar burning velocities using the spherical combustion bomb technique for methanol/'air' mixtures at 358 K. Veloo et al [21] experimentally determined the laminar flame speed of methanol using the counter-flow configuration technique at atmospheric pressure and at an unburned mixture temperature of 343 K. Vancoillie et al [22] reported laminar flame speed measurements at atmospheric pressure for methanol/'air' mixtures at unburned gas temperatures of 298-358 K using the heat flux method. What is absent for the most part in the previous studies is validation data for engine relevant conditions at pressures in the range 10-150 atm in the temperature range 800-1600 K. This study provides a comprehensive set of data in this regime and covers low-to high-temperature chemistry by coupling ST, RCM and JSR measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Laminar burning 150 velocity correlations for methanol and ethanol have been determined based on chemical kinetics calculations [31]. These correlations have been extensively validated against measurements obtained on two different fundamental combustion research setups [5,32,33]. Figure 1 shows that, compared to the older correlations of Metghalchi & Keck and Gülder, the methanol u l correlation developed by the current authors places the peak laminar burning velocity at a richer equivalence ratio and predicts a less steep decrease in u l for rich mixtures.…”
mentioning
confidence: 75%
“…They offer the potential of CO 2 neutral transport and increased energy security, while ameliorating engine performance and efficiency compared to fossil fuels thanks to a number of interesting properties [5,6]. The most significant interesting properties of light alcohols include: 35 • High heat of vaporization, which causes considerable charge cooling as the injected fuel evaporates.…”
Section: Light Alcohols As Si Engine Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have worked on the laminar burning velocity of methanol and ethanol mixtures, compiling data from the literature [21] and looking at numerical [21] as well as experimental [22] means to determine a suitable laminar burning velocity correlation. A laminar burning velocity correlation has been determined based on chemical kinetics calculations [21].…”
Section: Simulation Programmentioning
confidence: 99%